Long-term outcomes of intravitreal ranibizumab for neovascular age-related macular degeneration in a well defined region of the UK. Issue 2 (29th June 2015) - Buckle, Miranda; Donachie, Paul H J; Johnston, Robert L
Abstract : Aims: To study long-term, whole population 'real-world' clinical outcomes of ranibizumab therapy in treatment-naïve eyes for neovascular age-related macular degeneration. Methods: Data collected prospectively from a single centre serving a defined population using an electronic medical record included: demographics, Early Treatment Diabetic Retinopathy Study visual acuity (ETDRS VA) at all visits, injection dates, central 1 mm retinal thickness, and operative and postoperative complications. Results: 1483 eyes from 1278 patients were included in this study. The median age at the time of the patient's first injection was 82.5 years, 64.9% of patients were female, and another ocular pathology was present in 7.3% eyes. The baseline VA was 23–39, 40–54, 55–70 and >70 ETDRS letters for 17.3%, 23.1%, 42.7% and 16.9% of eyes, respectively. The median VA in all baseline VA groups improved after the loading phase but declined back to the baseline level by 2–5 years. The rate of endophthalmitis following intravitreal injection was 1 in 2124 injections. Conclusions: These long-term real-world data demonstrate that in general VA increases during the loading phase but returns to near baseline levels after 2–5 years of treatment for each baseline VA category. Patients should be identified and treated as early as possible, since presenting VA predicts the VA maintained after 5 years of treatment. National Institute of Health and Care Excellence guidance advising treatment only for eyes with vision below 70 letters does not promote best long-term VA outcomes for patients.